2021
DOI: 10.2196/24996
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning–Driven Models to Predict Prognostic Outcomes in Patients Hospitalized With Heart Failure Using Electronic Health Records: Retrospective Study

Abstract: Background With the prevalence of cardiovascular diseases increasing worldwide, early prediction and accurate assessment of heart failure (HF) risk are crucial to meet the clinical demand. Objective Our study objective was to develop machine learning (ML) models based on real-world electronic health records to predict 1-year in-hospital mortality, use of positive inotropic agents, and 1-year all-cause readmission rate. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
(55 reference statements)
1
23
0
Order By: Relevance
“…The authors in [27] proposed the SARIIqSq model to forecast COVID-19 transmission dynamics. Yang et al [28] proposed a new approach using the XGBoost algorithm to predict critical patients using biomedical and epidemiological data. From a collection of 300 clinical features, the researchers identified three key features from the clinical data of 2799 patients collected from Tongji Hospital in Wuhan.…”
Section: Related Workmentioning
confidence: 99%
“…The authors in [27] proposed the SARIIqSq model to forecast COVID-19 transmission dynamics. Yang et al [28] proposed a new approach using the XGBoost algorithm to predict critical patients using biomedical and epidemiological data. From a collection of 300 clinical features, the researchers identified three key features from the clinical data of 2799 patients collected from Tongji Hospital in Wuhan.…”
Section: Related Workmentioning
confidence: 99%
“…In particular, CNNs have dominated the field of computer vision, and numerous variations are created over time. First model to incorporate convolution as well as pooling layers into a NN was known as LeNet-533, and their publication established the fundamental elements of CNNs [17]. However, it wasn't until 2012 that a CNN programme dubbed AlexNet34, which took first place in the picture classification, began to dominate the ImageNet 2012 competition.…”
Section: Contribution Of This Research Is As Followsmentioning
confidence: 99%
“…Machine learning (ML) is a technique focused on how computers discover underlying patterns from high-dimensional and large datasets, which can be applied in clinical practice to develop efficient and robust predictive models ( 9 , 10 ). Many studies have shown that models based on ML have better performance than traditional statistical models using the Logistic Regression algorithm ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%